Optical coherence tomography imaging of potato skin to understand variability in response to pre- and postharvest factors - Landahl, Sandra; Foukaraki, S.; McWilliam, S.; Terry, Leon A. (International Society for Horticultural Science (ISHS), 2018)
In order to be able to assess the effect of pre- and postharvest treatments on different potato cultivars and tissues, information is needed on the skin architecture of tubers. Optical coherence tomography (OCT) was utilised as an appropriate non-destructive technique due to its high spatial resolution. It uses near-infra-red optical radiation to map the internal structures of semi-transparent samples. Samples in this study were potatoes with known provenance, under selected pre- or postharvest treatment. The study herein aimed to examine the effect of the growing environment and a desiccant chemical on skin layer development of several potato cultivars and to increase understanding of the variability in skin thickness after application of sprout suppressant. Different thicknesses of the skin layer were found between different farming locations, cultivars and spatial positions on individual tubers (60 to 100 µm). In detail, the spatial difference of skin layer thicknesses developed over time. Duration of the desiccation and curing did not cause significant differences in the skin thickness. However, skin thickness changes were observed during storage and were cultivar dependent. The chlorpropham treatment did not significantly influence the skin layer thickness. Still images recorded by means of OCT were a convenient and non-destructive tool to quantitatively evaluate the skin thickness of potatoes. In conclusion, the high resolution of the acquired still images allowed confirmation of tissue identification. It appears that the tissue position on the tuber may have a higher influence on the phellem thickness than the harvest date or curing.
Keywords: Desiccant; OCT; Eye movement; Solanum tuberosum; Phellem